Yield and quality of ginger (Zingiber officinale Rosc.) grown in Nagaland, India - KOTOKY, M G PATHAK, R S SINGH, P B KANJILAL, M N SARMA, I H SIDDQUE, R (Journal of Spices and Aromatic Crops, 1997)
Multilocational trials conducted at N agaland, India, in ginger (Zingiber officinale) indicated significant differences in growth characteristics and yield components among the cultivars at various locations. The yield was very low (4.8-9.3 t/ha) and fibre content high (6.7-9.6%) at all locations. Yield and quality of ginger grown in .Wokha, Mon, Mokokchang and Tuensang districts were superior to the ginger from other districts of N agaland.